Robotic sacrocolpopexy - Al-Otaibi Mozon; Ju Hee Kim; Sa Ra Lee (Korean Society of Obstetrics and Gynecology, 2024)
Pelvic organ prolapse (POP) is a common cause of gynecological disease in elderly women. The prevalence of POP has increased with an aging society. Abdominal sacrocolpopexy (ASC) is safer and more effective than the vaginal approach in patients with apical compartment POP because it has a higher anatomical cure rate, a lower recurrence rate, less dyspareunia, and improved sexual function. Laparoscopic sacrocolpopexy (LSC) has replaced ASC. Robotic sacrocolpopexy (RSC) also helps overcome the challenges of LSC by facilitating deep pelvic dissection and multiple intracorporeal suturing. The RSC is technically easy to apply, has a steep learning curve, and offers many advantages over the LSC. However, insufficient data led us to conclude that the LSC is superior overall, especially in terms of cost-effectiveness. The present review provides insights into different aspects of RSC, highlighting the most common benefits and concerns of this procedure. We searched for eligible articles discussing this issue from January 2019 to March 2022 to reveal the outcomes of RSC.